Duração do sono e controle glicêmico em pacientes com diabetes mellitus tipo 2 - Wagner José Martorina (2019)
For several years, science has been pointing to the importance of an adequate sleep for human health. Sleep duration (SD), when inadequate (short or long), is associated with an increased risk of diseases such as obesity, diabetes mellitus, cardiovascular diseases, some cancers and higher mortality. In patients with type 2 diabetes mellitus (T2DM), some studies have suggested an association between long and short sleep duration and worse glycemic control (GC). However, there are many controversies, from a methodological point of view, regarding these works. This is due to the fact that such association is complex, bidirectional and presents many possible mediating and confounding variables, not always considered simultaneously in these works. In view of this, this work aimed to answer the following question: is there an independent association between short / long SD and GC in outpatients with T2DM compared to intermediate SD? Using updated definitions of SD, we simultaneously considered all the confounding factors and mediators that emerged most recently in the literature: age, gender, diet, physical activity, obesity, night pain, nocturia, sleep quality, chronotype, obstructive sleep apnea (OSA), depressive symptoms, alcohol, caffeine, tobacco, number of annual consultations with endocrinologists, family history of T2DM and sleep medication. The study design was transversal; 140 outpatients with T2DM participated in the study, with ages ranging from 40 to 65 and glycohemoglobin (HbA1c) estimated glycemic target below 7%. The authors evaluated which variables, including HbA1c, were significantly associated with short (<6 hours) or long (> 8 hours) SD when compared to intermediate SD (6-8 hours). Results showed that higher levels of HbA1c increased the probability of belonging to the short SD group (p <0.001) and that a better sleep quality score, nocturia and greater tendency to maturity increased the probability of belonging to the long SD group (p <0.05). Based on the results, it was possible to conclude that there is an independent association between short SD and higher levels of HbA1c and that the association between long SD and HbA1c may be biased due to to variables not included in previous studies, especially OSA. Prospective studies could elucidate whether interventions in glycemic control could extend SD and improve the quality of life of patients with short SD, and also whether interventions in SD would be a new tool to improve the CG of patients with T2DM.